2022-RA-1009-ESGO Immune-related endpoints in patients with advanced or recurrent endometrial cancer treated with dostarlimab in the GARNET study. (20th October 2022) - Tinker, Anna V; Pothuri, Bhavana; Gilbert, Lucy; Sabatier, Renaud; Brown, Jubilee; Ghamande, Sharad; Mathews, Cara; O'Malley, David M; Boni, Valentina; Gravina, Adriano; Banerjee, Susana; Miller, Rowan E; et al.
Abstract : Introduction/Background: Dostarlimab is a programmed death 1 (PD-1) inhibitor approved in the US as monotherapy in patients with mismatch repair deficient (dMMR) advanced/recurrent endometrial cancer (EC) that has progressed on or after platinum-based chemotherapy or dMMR solid tumours that have progressed on or after prior treatment, with no satisfactory alternative treatment options; and in the EU as monotherapy in patients with dMMR/microsatellite instability-high (MSI-H) advanced/recurrent EC that has progressed on or after platinum-based chemotherapy. We report efficacy endpoints by immune-related RECIST (irRECIST) per investigator assessment (IA) for the EC cohorts of the GARNET trial. Methodology: GARNET is a multicentre, open-label, single-arm phase 1 study. Assignment to cohort A1 (dMMR/MSI-H EC) or A2 (mismatch repair proficient [MMRp]/microsatellite stable [MSS] EC) was based on local assessment. Patients received 500 mg of dostarlimab intravenously Q3W for 4 cycles, then 1000 mg Q6W until disease progression, discontinuation, or withdrawal. Immune-related endpoints (irORR, irDOR, and irPFS) were prespecified secondary endpoints. Results: The irRECIST efficacy-evaluable population included 152 patients with dMMR/MSI-H EC and 160 patients with MMRp/MSS EC with measurable disease at baseline and ≥6 months' follow-up per IA. irORR and irDOR were similar to the primary endpoints of ORR and DOR by BICR per RECIST v1.1 ( table 1 ). For dMMR/MSI-H, median irPFS was 11.2 mo versus median PFS of 6.0 mo, although the probability of remaining progression free at 6, 12, or 18 mo was similar. Safety was previously reported. Conclusion: In line with the study primary endpoints, secondary efficacy endpoints by irRECIST demonstrate the benefit of dostarlimab in patients with EC.